2021
DOI: 10.3390/jintelligence9030047
|View full text |Cite
|
Sign up to set email alerts
|

How Wisdom Emerges from Intellectual Development: A Developmental/Historical Theory for Raising Mandelas

Abstract: This paper invokes cognitive developmental theory as a means for preparing citizens to deal with and resolve conflicts within or across nations. We take the centuries-old Greek–Turkish dispute as an example. We first outline a theory of intellectual development postulating that mental changes emerge in response to changing developmental priorities in successive life periods, namely, interaction control in infancy, attention control and representational awareness in preschool, inferential control and cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Wisdom is a complex, multifaceted construct; how developmental resources contribute to its emergence over the life-span is a highly interesting topic for future research. In particular, more research is needed on the cognitive and noncognitive roots of wisdom in childhood (Demetriou et al, 2021; Jeste & Lee, 2019; Pasupathi et al, 2001) and the changing dynamic of cognitive wisdom resources in old age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wisdom is a complex, multifaceted construct; how developmental resources contribute to its emergence over the life-span is a highly interesting topic for future research. In particular, more research is needed on the cognitive and noncognitive roots of wisdom in childhood (Demetriou et al, 2021; Jeste & Lee, 2019; Pasupathi et al, 2001) and the changing dynamic of cognitive wisdom resources in old age.…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have reported correlations between intelligence and wisdom (see Intelligence Is a Necessary but Not Sufficient Condition for Wisdom section), there are few theoretical accounts of the relationship (but see Demetriou et al, 2021; Glück, 2020a; Tynjälä et al, 2020). Early on, some authors discussed wisdom as a form of postformal thinking (e.g., Arlin, 1990; Kitchener & Brenner, 1990; Labouvie-Vief, 1990; Pascual-Leone, 1990), but little empirical research has followed up on those ideas.…”
Section: What Is Wisdom and How Can It Be Measured?mentioning
confidence: 99%